2020
DOI: 10.3390/ijerph17030875
|View full text |Cite
|
Sign up to set email alerts
|

Changing Trends of HIV, Syphilis, and Hepatitis C among Male Migrant Workers in Chongqing, China: Nine Consecutive Cross-Sectional Surveys, 2010–2018

Abstract: Background: Male migrant workers (MMWs) have been reported to be vulnerable to human immunodeficiency virus (HIV) and other sexually transmitted infections (STIs). Chongqing, China is one of the major migration destinations and hotspots of HIV. This study aims to explore the prevalence of HIV, syphilis, and hepatitis C virus (HCV), as well as HIV-related knowledge and behaviors, among MMWs in Chongqing. Methods: Questionnaire surveys were conducted, and blood samples were collected and examined among MMWs sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…The southeast region in Sichuan has a high population density and accounts for a large amount of the migrant labor force in big cities all over the country. Research shows that migrant workers have a significant increase in engagement with sex workers and a low percentage of consistent condom use (Li et al, 2017;Wang et al, 2020). Molecular subtypes of HIV/AIDS prevalent among migrant workers in Sichuan are related to the subtypes in other provinces in China (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The southeast region in Sichuan has a high population density and accounts for a large amount of the migrant labor force in big cities all over the country. Research shows that migrant workers have a significant increase in engagement with sex workers and a low percentage of consistent condom use (Li et al, 2017;Wang et al, 2020). Molecular subtypes of HIV/AIDS prevalent among migrant workers in Sichuan are related to the subtypes in other provinces in China (Su et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, migrant illegal miners largely represent a group of sexually active men who are separated from their regular partners for extended periods. 19 The research participants reported prolonged periods of staying away from home ending up in extra marital relationship and sometimes catching sexual transmitted infections. Research has noted that the migrant nature of work is characterised by access to commercial sex work, high alcohol use and low condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Many adults continue to be sexually active throughout their lives. Among them, men living in urban areas nearing retirement are more likely to engage in unsafe sex [ 23 ]. Our study indicated that women of child-bearing age (20–39 years) are emerging as another vulnerable group of blood- and sexually transmitted infections, as their open-minded attitude toward sex and high-risk sexual behavior have increased the risk of spreading blood- and sexually transmitted diseases [ 24 ].…”
Section: Discussionmentioning
confidence: 99%